Analisis Pengembangan Pariwisata Halal Pada Destinasi Taman Wisata Laut Desa Labuhan, Kecamatan Sepulu, Kabupaten Bangkalan, Madura - Kurniyati Indahsari; Retno Dwi Wulandari (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
The study purpose was to confirm the Marine Tourism Park condition with the halal tourism development based on the DSN-MUI Fatwa. This was a qualitative descriptive research using phenomenology. While previous researches were focused on the tourism components condition only or their conformity with criterias of Global Muslim Muslim Travel Indeks, this research was focused on the tourism components condition, including Attraction, Amenity, Accessibility, and Hospitality as well as their conformity with the DSN-MUI Fatwa. The results show that Marine Tourism Park can be developed into halal tourism. The Attraction, namely its uniqueness, benefits, security, cultural development, and attractions, are meet the Fatwa. The discrepancy in is in the cleanliness, comfort as well as the presence of adultery. The Amenity, namely the availability of facilities are meet the fatwa. The discrepancy is in the damage of some facilities and the lack of worship, security and clean water facilities. While all Hospitality components are meet the Fatwa, all Accessibility components are not. This research novelty is the recommendations on tourism sub components which should be fulfilled by The Marine Tourism Park to become a Halal tourism